(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Effective hospital care requires seamless coordination among diverse healthcare professionals, with nursing technicians, radiology technicians, pharmacy technicians, and social workers playing pivotal roles in optimizing patient outcomes, workflow efficiency, and safety. Nursing technicians provide frontline patient care and facilitate clinical communication, while pharmacy technicians ensure safe and accurate medication management. Radiology technicians contribute essential diagnostic services, and social workers address psychosocial needs, supporting patient adherence and overall wellbeing. The integration of these professionals enhances interdisciplinary collaboration, reduces errors, improves resource utilization, and addresses complex ethical and operational challenges inherent to hospital settings. Aim of Work: This study aims to examine the impact of integrated care models on patient outcomes, workflow efficiency, and safety, focusing on the coordinated efforts of nursing technicians, radiology technicians, pharmacy technicians, and social workers. Additionally, it investigates ethical concerns, professional accountability, operational challenges, and interprofessional communication barriers associated with implementing collaborative care models in diverse hospital environments. Methods: A mixed-method approach was employed, combining structured questionnaires, semi-structured interviews, focus group discussions, and direct observational analysis. Participants included nursing technicians, radiology technicians, pharmacy technicians, social workers, and other hospital staff across multiple departments. Data collection focused on evaluating the effectiveness of interdisciplinary collaboration in optimizing patient care, ensuring medication safety, streamlining workflows, addressing psychosocial needs, and enhancing interprofessional communication. Triangulation of quantitative and qualitative data provided comprehensive insights into the practical, cognitive, and ethical dimensions of integrated care models. Findings: The study revealed that interdisciplinary collaboration significantly improved workflow efficiency, accuracy of diagnostic and medication-related processes, and patient-centered outcomes. Integration of nursing, pharmacy, radiology, and social work services reduced errors, enhanced adherence to treatment protocols, and improved patient satisfaction. Participants reported improved communication, shared accountability, and a better understanding of each professional’s role in patient care. Ethical concerns, including role boundaries, confidentiality, informed consent, and equitable resource allocation, were identified as critical areas requiring careful attention to ensure safe and effective implementation of collaborative care models. Conclusion: Integrating nursing technicians, radiology technicians, pharmacy technicians, and social workers within coordinated care models represents an effective, patient-centered strategy for enhancing hospital care quality, safety, and efficiency. Structured interdisciplinary collaboration promotes accurate diagnosis, safe medication management, optimized workflow, and holistic patient support, while addressing ethical and operational challenges. Institutional support, continuous training, and clearly defined roles are essential to sustain high-quality outcomes and foster a culture of accountability and interprofessional collaboration.